2019
DOI: 10.1242/jeb.187179
|View full text |Cite
|
Sign up to set email alerts
|

Ocean warming combined with lower omega-3 nutritional availability impairs the cardio-respiratory function of a marine fish

Abstract: Highly unsaturated fatty acids of the omega-3 series (HUFA) are major constituents of cell membranes, yet are poorly synthesised de novo by consumers. Their production, mainly supported by aquatic microalgae, has been decreasing with global change. The consequences of such reductions may be profound for ectotherm consumers, as temperature tightly regulates the HUFA content in cell membranes, maintaining their functionality. Integrating individual, tissue and molecular approaches, we examined the consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…We used these two cleaned contigs as reference genomes to map Illumina 2 × 150 bp HiSeq sequences (data quality control and pre-processing step as in 78 ) produced from a second individual using Pilon 1.21 79 . HiSeq sequencing of cDNA was performed based on mRNAs purified from sperm and foot tissue (for mapping onto the male and female mitogenomes, respectively) using the Macherey-Nagel Nucleospin RNA kit for NucleoZOL (RNA quality control, cDNA synthesis, library preparation, sequencing, data quality control and pre-processing as in 80 ). By mapping high-quality Illumina reads on our draft nanopore contigs, we were able to further correct sequencing errors.…”
Section: Methodsmentioning
confidence: 99%
“…We used these two cleaned contigs as reference genomes to map Illumina 2 × 150 bp HiSeq sequences (data quality control and pre-processing step as in 78 ) produced from a second individual using Pilon 1.21 79 . HiSeq sequencing of cDNA was performed based on mRNAs purified from sperm and foot tissue (for mapping onto the male and female mitogenomes, respectively) using the Macherey-Nagel Nucleospin RNA kit for NucleoZOL (RNA quality control, cDNA synthesis, library preparation, sequencing, data quality control and pre-processing as in 80 ). By mapping high-quality Illumina reads on our draft nanopore contigs, we were able to further correct sequencing errors.…”
Section: Methodsmentioning
confidence: 99%
“…While it was not within the scope of this study, other important performance traits may have differed between the diet treatments. These include, but are not limited to, differences in Journal of Experimental Biology • Accepted manuscript microbiome diversity and function, visual acuity, cognitive ability, digestion efficiency and digestive costs relative to aerobic scope, immune function, aerobic swimming performance, and cardiac stroke volume (Glencross and Rutherford, 2010;Koven et al, 2018;Vagner et al, 2014Vagner et al, , 2019b. It remains unclear whether opaleye and other omnivorous ectotherms consume different proportions of plant: animal to regulate their thermal responses.…”
Section: Performance Costs and Benefits For Diet Choice At Different Acclimation Temperaturesmentioning
confidence: 99%
“…Chung et al (2018) recently reported that changes in phospholipid FA composition are the primary signature of thermal acclimation in killifish (Fundulus heteroclitus) and that these changes are linked to hepatic mitochondrial performance. Furthermore, Vagner et al (2019) showed that the highly unsaturated fatty acid (HUFA) content of cell membranes, which is known to be tightly regulated by temperature (Pethybridge et al, 2015), influences the cardiorespiratory function of marine fishes. Yet, the effect of hypoxia acclimation on mitochondrial membrane FA composition and fluidity in fishes, and thus on mitochondrial function and performance, have also not been examined.…”
mentioning
confidence: 99%